COVID-19 and Air Quality: Evidence from China. Issue 10 (8th August 2020) - Ming, Wen; Zhou, Zhengqing; Ai, Hongshan; Bi, Huimin; Zhong, Yuan
ABSTRACT: To test the impact of the COVID-19 pandemic on air quality, this article matches the city-level real-time air quality monitoring data with the big data on population migration provided by Baidu. The article uses urban samples from the same data sample of the Chinese lunar calendar in 2019 to construct the counterfactual status of the COVID-19 pandemic. Then, the difference-in-differences (DID) model is employed to estimate the impact of the COVID-19 pandemic on air quality. It is found that the COVID-19 pandemic caused PM2.5 and AQI to decrease by about 7 μg/m 3 and 5-points, respectively.